منظمة شنغهاي للتعاون SCO نشأتها - اعضائها - دورها الاقليمي والدولي - حسن فاضل عبدعلي (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The Shanghai Cooperation Organization (SCO) is among the most important regional and international organizations established and established through the five-year Shanghai Agreement signed on April 26, 1996 by (China, Russia, Kazakhstan, Kyrgyzstan and Tajikistan) in the Chinese city of Shanghai, at the invitation of China and Russia, after the dissolution of the Soviet Union And the problems faced by the Russian Federation and the countries that separated from this union, especially in the continent of Asia, and the accompanying attempt by the United States of America and NATO to extend their influence and influence to this region, which prompted both Russia and China to coordinate their efforts to limit American and Western influence in the regions. their influence and in the Central Asian region in particular, In addition to resolving the border disputes between China and the republics of the former Soviet Union adjacent to it, in addition to deepening military cooperation between the parties, achieving cooperation in various security, political, economic and cultural fields, and combating extremism, terrorism and separatist movements, and later Uzbekistan joined as well as India and Pakistan with full membership.